'Pointing the way': Alex Bloom and A.S. Neill on the enduring necessity and enacted possibility of radical democratic education as 'a method of life'. Issue 6 (7th October 2022) - Fielding, Michael
Abstract: Prompted by the centenary of the founding of Summerhill, in my contribution to this JOPE Suite on Democratic Education, I briefly explore both the admiring reciprocity and the subsidiary but significant differences of praxis between A.S. Neill and Alex Bloom, two remarkable pioneers of education in and for participatory democracy as a way of life. Because A.S. Neill's work is internationally renowned and Alex Bloom's has yet to re-establish the worldwide recognition it had in his own lifetime, my emphasis is on the contribution of Alex Bloom, in large part because he is amongst the most radical pioneers of democratic education the UK state sector has ever known. To a significant degree, the aspirations and actualities of Bloom's work rebutted Neill's insistence that pioneers within the state sector of education could not innovate in ways that would significantly challenge the status quo. Indeed, Alex Bloom extended participatory democratic educational aspirations in ways which Neill did not. Most importantly, these not only entailed a commitment to community engagement, they did so in conditions of abject poverty and profound psychological trauma following the ravages of the Second World War London Blitz with its attendant evacuation and subsequent return to the ruins of their former homes. In the first section, I take as my starting point Alex Bloom's strongly supportive review of A.S. Neill's book The Problem Family and Neill's visit to Bloom's school in the East End of London, some five years later. Foregrounding the dialectic of practice and aspiration, I touch on some of the key issues that emerged for both Neill and Bloom at that time. Challenging Neill's later affirmation that the only significant freedom one can introduce into a state school is 'a free attitude on the teacher's part, his or her being on the side of the child' and his reported view that Bloom and others might be able to experiment in methods of teaching or ways of organising the timetable, 'but not in methods of living', the second section explores the nature and interrelationship of six key strands woven into the fabric of Alex Bloom's truly remarkable work that exemplified the grounded possibility and vibrant actuality of participatory democracy as a way of living and learning together that prefigures a more just, creative and caring form of human engagement. Locating the foundation of Alex Bloom's praxis within the 20th-century personalist philosophical tradition and its Adlerian psychological counterpart, the brief concluding section draws in particular on the work of John Macmurray who argues, as did Bloom in his own writing and his daily praxis, that 'The first priority in education—if by education we mean learning to be human—is learning to live in personal relation to other people. Let us call it learning to live in community'.